(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article explores the methodology of developing preschool children’s understanding of geometric shapes within early childhood education settings. Emphasis is placed on ageappropriate pedagogical strategies, visual aids, and interactive methods that support cognitive and spatial development. The study examines both theoretical foundations and practical approaches used by educators to foster children’s ability to recognize, differentiate, and name basic geometric shapes such as circles, squares, and triangles. It also highlights the importance of integrating geometric concepts into play-based learning to enhance engagement and comprehension. The article considers the specific context of preschool institutions in Uzbekistan and outlines culturally relevant educational tools and techniques.